REVITALISASI NILAI-NILAI PANCASILA DI ERA GLOBALISASI MELALUI PENDIDIKAN PANCASILA DI PERGURUAN TINGGI - Julianty, Annisa Azzahra; Dewi, Dinie Anggraeni (Universitas Tanjungpura, 2022)
This research basically aims to describe efforts to revive the noble values of Pancasila in the era of globalization. This research shows that in reviving the noble values of Pancasila can be pursued through Pancasila Education courses in universities. Pancasila as the basis of the state is a way of life for every human being, nation and state. Seeing the phenomena that exist in the global era, not a few Indonesian people have forgotten the values of Pancasila. It is a threat and a challenge if the noble values of Pancasila begin to erode. We can understand together that Pancasila education is the basic capital to restore the identity of the Indonesian nation which is increasingly being eroded due to the flow of globalization. Pancasila education also basically provides an accurate understanding of the meaning of Pancasila values. Revitalizing the values of Pancasila can be done by rebuilding the value of local wisdom in accordance with the values of Pancasila. Therefore, efforts are needed in rebuilding the values of Pancasila to prevent negative understandings and influences that arise due to the swift currents of globalization.